Posted by
**jasmine20** on
.

I need help can someone help me get unstuck and let me know if i am correct.thank you.

solve by completing the square.

4x^2+2x-3=0

this is what i am doing:

i used the quadratic equation.

so where i am is in this step:

x = (-2 (+-) sqrt (-44))/(8)

from this point i am stuck:

Problem #2

Solve by using the quadratic equation :

5x^2-4x+1=0

this is where i have almost the last step but i am not sure:

x = (4 (+-) sqrt (-4))/(10)

x= (2 +-sqrt )2))/(5)

The first says...complete the square, you did not do that.

4x^2+2x-3=0

4x^2+ 2x = 3

x^2 + 1/2 x = 3/4

Now we add 1/4 to each side

x^2 + 1/2 x + 1/4 = 1

(x+1/2)^2= 1

square root of each side...

x+ 1/2 = +- 1

x= -1/2 +-1

5x^2-4x+1=0

a= 5 b= -4 c= 1

x= (4+-sqrt (16-20) )/10

x= .4 +- 1/10 sqrt-4

x= .4 +- .2i where i is the sqrt-1